2013
DOI: 10.1177/0003319713514290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Upstream Administration of Tirofiban Before Percutaneous Coronary Intervention on Spontaneous Reperfusion and Clinical Outcomes in Acute ST-Segment Elevation Myocardial Infarction

Abstract: We assessed the effects of upstream administration of the glycoprotein IIb/IIIa inhibitor tirofiban before percutaneous coronary intervention (PCI) on spontaneous reperfusion (SR) of infarct-related artery (IRA) and the clinical outcomes in patients with ST-segment elevation myocardial infarction (STEMI). The incidence of SR of the IRA was significantly higher in the tirofiban group than in the no-tirofiban group (141 [36.5%] vs 21 [17.2%], P < .001). By multivariate logistic regression analysis, use of tirofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…According to these studies, the 2012 ESC guideline defined that there is no definitive answer regarding the current role of the routine use of GP IIb/IIIa inhibitors in primary PCI in the era of potent DAPT, particularly when prasugrel or ticagrelor is used (5). On the other hand, recent studies (6, 7) of tirofiban with DAPT in STEMI support the findings of Kaymaz et al (1) Tirofiban administered with primary PCI following the administration of 600 mg clopidogrel improved the primary efficacy outcome at 30-day and 1-year follow-up without an increase in major bleeding. Zhu et al (7) demonstrated that the upstream use of tirofiban is significantly associated with an increased incidence of spontaneous reperfusion and a decreased incidence of MACE at 30-day as well as 90-day follow-up in patients treated with primary PCI for STEMI.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…According to these studies, the 2012 ESC guideline defined that there is no definitive answer regarding the current role of the routine use of GP IIb/IIIa inhibitors in primary PCI in the era of potent DAPT, particularly when prasugrel or ticagrelor is used (5). On the other hand, recent studies (6, 7) of tirofiban with DAPT in STEMI support the findings of Kaymaz et al (1) Tirofiban administered with primary PCI following the administration of 600 mg clopidogrel improved the primary efficacy outcome at 30-day and 1-year follow-up without an increase in major bleeding. Zhu et al (7) demonstrated that the upstream use of tirofiban is significantly associated with an increased incidence of spontaneous reperfusion and a decreased incidence of MACE at 30-day as well as 90-day follow-up in patients treated with primary PCI for STEMI.…”
supporting
confidence: 59%
“…On the other hand, recent studies (6, 7) of tirofiban with DAPT in STEMI support the findings of Kaymaz et al (1) Tirofiban administered with primary PCI following the administration of 600 mg clopidogrel improved the primary efficacy outcome at 30-day and 1-year follow-up without an increase in major bleeding. Zhu et al (7) demonstrated that the upstream use of tirofiban is significantly associated with an increased incidence of spontaneous reperfusion and a decreased incidence of MACE at 30-day as well as 90-day follow-up in patients treated with primary PCI for STEMI. I appreciate the authors for highlighting the use of tirofiban with DAPT in STEMI patients.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…However, expansion of balloon and stimulating effect of metal stents can cause endothelial injury, platelet activation and aggregation, adhesion, and lead to acute vascular occlusion and coronary artery embolism formation after PCI operative. Therefore, antiplatelet therapy was a very important part of PCI therapy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%